Tanggung Jawab Penyedia Layanan Jasa Kursus Mengemudi Mobil dalam kecelakaan Lalu Lintas - Dyah Merryani; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2021)
Car driving courses are tutoring related to driving skills that aim to provide knowledge of how to drive a car to course service users. Course service users are accompanied and trained by the instructor during the driving course. However, users of course services with instructors will be faced with unexpected events, which often occur, namely traffic accidents. The purpose of this research is to uncover the legal relationship that occurs between car driving course service providers and instructors and also the course service users form the responsibility of the car driving course service provider if an accident occurs during the driving course. This research is an empirical legal research with a sociological juridical approach and a statutory approach. The data collection technique was done by interview. Sources of data used in this research are primary data sources and secondary data sources. After the data was collected, it was analyzed systematically. The results of this research indicate that there is a legal relationship between the parties involved, namely the working relationship that occurs between the instructor and the driving course service provider, and the agreement from the course service user through filling out the course registration form to the driving course service provider. The occurrence of a traffic accident during the driving course practice will be accounted for by the driving course service provider as the employer and the instructor as a companion or trainer for the course service user during the driving course.